The effects of COVID-19 restrictions and other perinatal factors on women's sense of control during childbirth: a prospective cohort study. (2nd October 2022) - Chaibekava, Karina; Scheenen, Amber; Lettink, Adrie; Smits, Luc; Langenveld, Josje; van de Laar, Rafli; Peeters, Babette; Joosten, Sanne; Verstappen, Marie-Louise; Nieuwenhuijze, Marianne; Scheepers, Hubertina
Abstract: Background: Restrictions around childbirth, introduced during the COVID-19 pandemic in 2020, could decrease maternal feelings of control during birth. The aim of this study was to compare the sense of control of women who gave birth during the COVID-19 pandemic with women who gave birth before COVID-19. The secondary objective was to identify other factors independently associated with women's sense of control during birth. Methods: A prospective cohort study, in a sub-cohort of 504 women from a larger cohort (Continuous Care Trial (CCT), n = 992), was conducted. Sense of control was measured by the Labor Agentry Scale (LAS). Perinatal factors independently associated with women's sense of control during birth were identified using multiple linear regression. Results: Giving birth during the COVID-19 pandemic did not influence women's sense of control during birth. Factors statistically significantly related to women's sense of control were Dutch ethnic background ( β 4.787, 95%-CI 1.319 to 8.254), antenatal worry ( β − 4.049, 95%-CI −7.516 to −.581), antenatal anxiety ( β − 4.677, 95%-CI −7.751 to 1.603) and analgesics during birth ( β − 3.672, 95%-CI −6.269 to −1.075). Conclusions: Despite the introduction of restrictions, birth during the COVID-19 pandemic was not associated with a decrease of women's sense of control.